Investing in mutual funds when returns are predictable - Doron Avramov; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2005)
This paper analyzes the performance of portfolio strategies that invest in noload, open-end U.S. domestic equity mutual funds, incorporating predictability in (i) manager skills, (ii) fund risk-loadings, and (iii) benchmark returns. Predictability in manager skills is found to be the dominant source of investment profitability - long-only strategies that incorporate such predictability considerably outperform prior-documented hot-hands and smart-money strategies, and generate positive and significant performance with respect to the Fama-French and momentum benchmarks. Specifically, these strategies outperform their benchmarks by 2-4% per year through their ability to time industries over the business cycle. Moreover, they choose individual funds that outperform their industry benchmarks to achieve an additional 3-6% per year. Overall, our findings indicate that industries are important in locating outperforming mutual funds, and that active management adds much more value than documented by prior studies.
Keywords: 330